MEDIA PEMBELAJARAN HERBARIUM BERBASIS SAINTIFIK TERHADAP KEMAMPUAN MENGENAL MORFOLOGI TUMBUHAN PADA SISWA TUNANETRA KELAS IV SEKOLAH DASAR LUAR BIASA - Putri Wulandari, Islami (Jurnal Pendidikan Khusus, 2017)
Abstrack : The ability of recognizing and forming perception of concrete form of plantation morphology to blind children was a difficult thing if the educator did not use a learning media. The usage of herbarium learning media for blind students needed to be done to enhance the learning result of blind students. In this research, herbarium learning media used for blind students was to recognize the plantation morphology. The plantation morphology recognized involved root, stem, leaf, and flower. The application of herbarium learning media in this research based on the scientific so the learning implementation did not take off the activities of observing, asking, trying, reasoning, and communicating. This research method was quantitative kind and the data was collected by pre-test and post-test. The pre-test and post-test were used to obtain the data of recognizing plantation morphology ability to blind students before and after giving the application of learning media. The research result was obtained from the results of pre-test and post-test. It was obtained the pre-test result was 50,83 and the post-test result was 84,17. In this way, it could be concluded that Z counted = 2,28 was compared to the critic value 5% Z table = 1,96. The result indicated that Z counted was greater than Z table (Zh > Zt) meaning Ho was refused and Ha was accepted so it could be stated that there was significant influence of herbarium learning media application based scientific toward recognizing plantation morphology ability to the blind students of class IV in SDLB-A YPAB Surabaya.     Keywords: Herbarium learning media, scientific, plantation morphology.